Effect of refrigerant on the exergy loss and performance in air conditioner using ejector as expansion device - Serevina, Vina (2015)
This paper presents a numerical approach to determine the exergy loss in an air conditioner using (A/C) R22 and R290 as working fluid. The exergy loss should be minimized in order to increase the performance of the air conditioner. The present study investigates the A/C with cooling capacity of 2.4 kW. The results show that the total exergy loss of R290 is lower than that of R222, viz. 0.667 and 0.857 kW, respectively. This indicates that the use of R290 in the air conditioner using ejector as expansion device will generate a better COP improvement than that of R22. In addition, energy analysis shows that the COP improvements using R290 is higher than that of R22, for instance, 12.24 and 8.15% for R290 and R22, respectively, at the ambient temperature of 35°C.